Impact of the Consumption of Tea Polyphenols on Early Atherosclerotic Lesion Formation and Intestinal Bifidobacteria in High-Fat-Fed ApoE−/− Mice - Liao, Zhen-Lin; Zeng, Ben-Hua; Wang, Wei; Li, Gui-Hua; Wu, Fei; Wang, Li; Zhong, Qing-Ping; Wei, Hong; Fang, Xiang (Frontiers in Nutrition, 2016)
There is an increasing interest in the effect of dietary polyphenols on the intestinal microbiota and the possible associations between this effect and the development of some cardiovascular diseases, such as atherosclerosis (AS). However, limited information is available on how these polyphenols affect the gut microbiota and AS development. This study was designed to evaluate the modulation of dietary tea polyphenols(TP) on intestinal Bifidobacteria(IB)and its correlation with AS development in apolipoprotein E-deficient (ApoE-/-) mice. Fifty C57BL/6 ApoE-/- mice were randomized into one of five treatment groups(n=10/group): control group fed normal diet (CK) ; a group fed a high-fat diet (HFD) and the other 3 groups fed the same high-fat diet supplemented with tea polyphenols in drinking water for 16 weeks. The total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were decreased significantly (P<0.05) after TP interference. In addition, the TP diet also decreased the patch area/lumen area (PA/LA) ratios (P<0.01) in the TP diet group. Interestingly, copies of IB in the gut of ApoE-/- mice were notably increased with TP interference. This increase was dose dependent (P<0.01), and negatively correlated with the PA/LA ratio (P<0.05). We conclude that tea polyphenols could promote the proliferation of the IB, which is partially responsible for the reduction of atherosclerosis plaque induced by high-fat diet.